2021
DOI: 10.1038/s41467-021-21129-z
|View full text |Cite
|
Sign up to set email alerts
|

AA amyloid fibrils from diseased tissue are structurally different from in vitro formed SAA fibrils

Abstract: Systemic AA amyloidosis is a world-wide occurring protein misfolding disease of humans and animals. It arises from the formation of amyloid fibrils from serum amyloid A (SAA) protein. Using cryo electron microscopy we here show that amyloid fibrils which were purified from AA amyloidotic mice are structurally different from fibrils formed from recombinant SAA protein in vitro. Ex vivo amyloid fibrils consist of fibril proteins that contain more residues within their ordered parts and possess a higher β-sheet c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 52 publications
3
81
0
Order By: Relevance
“…The first one attributes encountered differences in proteolytic susceptibility to differences in the fibril structure, which is supported by studies revealing structural differences between ex vivo and in vitro fibrils [1316,1820]. The different fibril structures may be associated with different thermodynamic stabilities of the fibrils, although protease resistant mouse AA amyloid fibrils were recently found not to be very stable to guanidine denaturation [18]. The second one is associated with the fact that ex vivo amyloid fibrils can contain non-fibril components of amyloid tissue deposits, such as SAP, which was previously found to protect amyloid fibrils from being degraded in vitro [33] and in vivo [32].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The first one attributes encountered differences in proteolytic susceptibility to differences in the fibril structure, which is supported by studies revealing structural differences between ex vivo and in vitro fibrils [1316,1820]. The different fibril structures may be associated with different thermodynamic stabilities of the fibrils, although protease resistant mouse AA amyloid fibrils were recently found not to be very stable to guanidine denaturation [18]. The second one is associated with the fact that ex vivo amyloid fibrils can contain non-fibril components of amyloid tissue deposits, such as SAP, which was previously found to protect amyloid fibrils from being degraded in vitro [33] and in vivo [32].…”
Section: Discussionmentioning
confidence: 95%
“…Several studies previously showed that disease-associated amyloid fibrils from patient tissue are structurally different from fibrils formed from the same polypeptide chain in vitro [1316,1820]. In two cases, namely murine SAA1.1 protein and human Aβ peptide, it was additionally found that ex vivo fibrils are more protease resistant than in vitro fibrils [16,18]. These observations led to the hypothesis that disease-associated amyloid fibrils were selected inside the body by their proteolytic stability [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed amplified sample is thus not directly taken from human tissue but is a more indirect representation of invivo structures than ex-vivo structures. Interestingly, none of the few known exvivo fibril structures have been observed either in-vitro or in amplified patientderived samples, yet (102,107). Nonetheless, in-vitro structures have broadened our understanding of amyloid architecture in general and revealed common structural features such as the amyloid key, which has been observed invitro and in-vivo and they furthermore help to interpret aggregation kinetics (108,109).…”
Section: 1sample Preparation For Amyloids Moves Closer To In-vivo Conditionsmentioning
confidence: 99%
“…It has been suggested that amyloid proteins such as Aβ and αSyn can form oligomerssupramolecular structures consisting of several noncovalent assemblies [19] and characterized by structural diversity [20] due to the partial enrichment of β-sheet structures, which may define the neurotoxicity of oligomers [21]. Still, the relative contribution of amyloid-specific secondary structures to neurotoxicity remains unknown.…”
Section: Introductionmentioning
confidence: 99%